Identification of QTL controlling high levels of partial resistance to Fusarium solani f. sp. pisi in pea. Issue 4 (29th June 2015) - Coyne, Clarice J.; Pilet‐Nayel, Marie‐Laure; McGee, Rebecca J.; Porter, Lyndon D.; Smýkal, Petr; Grünwald, Niklaus J.; Link, W.
Abstract Fusarium root rot is a common biotic restraint on pea yields, and genetic resistance is the most feasible method for improving pea production. This study was conducted to discover quantitative trait loci (QTL) controlling genetic partial resistance to Fusarium root rot caused by Fusarium solani (Mart.) Sacc. f.sp. pisi (F.R. Jones) W.C. Snyder & H.N. Hans (Fsp). A RIL population was screened in a Fusarium root rot field disease nursery for 3 years. Composite interval mapping was employed for QTL detection using the means of disease severity from three growing seasons. Five QTL were identified, including one QTL identified in all three years. The multiyear QTL Fsp‐Ps2.1 contributed to a significant portion of the phenotypic variance (22.1–72.2%), while a second QTL, Fsp‐Ps6.1, contributed 17.3% of the phenotypic variance. The other single growing season QTL are of additional interest as they colocate with previously reported pea–Fusarium root rot resistance QTL. QTL Fsp‐Ps2.1, Fsp‐Ps3.1, Fsp‐4.1 and Fsp‐Ps7.1 are flanked by codominant SSRs and may be useful in marker‐assisted breeding of pea for high levels of partial resistance to Fsp.